The Role of Acehnese Women in Dealing With the Corvid-19 Pandemic Phenomenon - Alwi Alwi; Taufik Abdullah; Muhammad bin Abubakar (Malikussaleh Social and Political Reviews, 2022)
The phenomenon of corvid 19 is a phenomenon that affects people's social changes to get used to a new social order called the "new normal". In an effort to reduce the number of people affected by corvid 19, the government has made various efforts through programs to comply with established health protocols. On the other hand, the success of suppressing the spread of corvid 19 is influenced by the role of women in prohibiting families from leaving the house and educating them to comply with health protocols set by the government. This study uses ground theory by paying attention to the behavior shown by the research subjects in achieving the corvid 19 phenomenon. The research approach carried out uses a qualitative approach that makes Acehnese women the object of research. The results showed that Acehnese women were able to provide stimulus in order to suppress the spread of corvid 19 during the pandemic. A different attitude is shown in the vaccination program, where Acehnese women experience a situation of distrust due to news information and government policies that are considered inconsistent.